Asymmetric total synthesis of (+)-(2R, 4′R, 8′R)-α-tocopherol enabled by enzymatic desymmetrization. Issue 14 (24th March 2022) - Yang, Haidi; Liu, Jinyao; Hu, Pan; Gao, Liang; Huang, Zedu; Chen, Fener
Abstract : Lipase-catalyzed desymmetric hydrolysis enabled an efficient, stereoselective synthesis of chiral diol ( S )-14, the key intermediate to (+)-(2 R, 4′ R, 8′ R )-α-tocopherol (1 ). Abstract : A new and highly stereoselective synthesis of chiral diol ( S )-14, the common synthetic intermediate to (+)-(2 R, 4′ R, 8′ R )-α-tocopherol (1 ), was accomplished in seven steps with 13.8% overall yield. This developed route featured a lipase-catalyzed desymmetric hydrolysis of prochiral diester 39a, which was prepared through a challenging Heck coupling, to chiral quaternary carbon-containing monoester ( R )-37a of the correct configuration in 81% yield and 96.7% ee, to the best of our knowledge, leading to the most efficient enzymatic desymmetric synthesis of the chiral chroman skeleton of vitamin E members reported to date. Coupled with the modified preparation of the phytol-derived side chain, the chemoenzymatic total synthesis of 1 was completed in 15 longest linear steps with 3.1% overall yield.